Kemampuan Mahasiswa Program Studi Bahasa dan Sastra Indonesia FKIP Universitas Jambi dalam Mendeskripsikan Istilah/Kosa Kata yang Muncul pada Mata Kuliah Morfologi - Zulfa, Nabila Khurriyatu; Setyonegoro, Agus; Rasdawita, Rasdawita (Jurnal Ilmiah Dikdaya, 2024)
This research is motivated by the low language skills of students which influence their interest in readingand so on. This has a negative impact on learning outcomes both inside and outside formal institutions. This researchaims to determine the ability of Indonesian Language and Literature Education Study Program students to describethe morphological terms/vocabulary they have studied. The method used was qualitative with a descriptive approachthrough interviews with resource persons at PBSI FKIP Jambi University class of 2021. The research results showedthat low language skills and interest in reading had an influence on participants' learning outcomes. It is hoped thatthis research can contribute to the field of education, especially as input for students and curriculum improvement.